2021
DOI: 10.1007/s10549-021-06193-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genomic assessment of PD-L1 SP142 expression in triple-negative breast cancer

Abstract: Purpose The SP142 PD-L1 assay is a companion diagnostic for atezolizumab in metastatic triple-negative breast cancer (TNBC). We strove to understand the biological, genomic, and clinical characteristics associated with SP142 PD-L1 positivity in TNBC patients. Methods Using 149 TNBC formalin-fixed paraffin-embedded tumor samples, tissue microarray (TMA) and gene expression microarrays were performed in parallel. The VENTANA SP142 assay was used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
1
18
1
Order By: Relevance
“…7-11 13 14 The efficacy of ICIs is affected by the subtypes of tumor microenvironments (TMEs). [35][36][37] It has been reported that the TMEs can be clustered into three groups: immune-desert type that lacks lymphocyte Open access infiltration, innate immune-inactivated type that infiltrated with inactivated innate immune cells and immuneinflamed type that infiltrated with high numbers of innate and adaptive immune cells. 38 Only the immune-inflamed type TME is predicted to benefit from ICI therapies, 38 which limits the efficacy of ICIs for TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…7-11 13 14 The efficacy of ICIs is affected by the subtypes of tumor microenvironments (TMEs). [35][36][37] It has been reported that the TMEs can be clustered into three groups: immune-desert type that lacks lymphocyte Open access infiltration, innate immune-inactivated type that infiltrated with inactivated innate immune cells and immuneinflamed type that infiltrated with high numbers of innate and adaptive immune cells. 38 Only the immune-inflamed type TME is predicted to benefit from ICI therapies, 38 which limits the efficacy of ICIs for TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the frequency of PD-L1 expression was higher in ICs in patients with node-negative status. In triple-negative BC, PD-L1 positive tumors have more immunogenic characteristics, including elevated tumor infiltrating lymphocyte (TIL) and CD8 counts, enrichment of the immunogenic genomic subtype, and elevated immunogenic gene signatures at the gene expression level [ 47 ]. However, it is not clear whether these characteristics could determine the occurrence of tumors at older ages or early stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether these characteristics could determine the occurrence of tumors at older ages or early stages. It should be noted that the SP142 assay detects more ICs and fewer TCs compared to the other assays, which can generate conflicting results depending on the PD-L1 assay utilized [ 47 ]. Furthermore, the interobserver agreement for PD-L1 expression in ICs is inferior to TCs in various types of tumors regardless of the type of assay used, which could also contribute to the divergence of prognostic factors [ 3 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…As TNBCs with high TILs are more likely to contain ≥1% PD-L1-positive immune cells [ 45 ], a combined evaluation of TILs and PD-L1 expression in locally advanced and metastatic TNBC has been proposed by the International Immuno-Oncology Biomarker Working Group to reduce the risk of suboptimal patient selection for immunotherapy [ 19 ]. Suboptimal patient selection might result from inter-pathologist variability in the PD-L1/SP142 assessment.…”
Section: Discussionmentioning
confidence: 99%